Efeitos da urbanização sobre a estrutura das assembleias de peixes em córregos urbanos Neotropicais. - Cunico, Almir Manoel (2010)
This study aimed to observe patterns in the taxonomic and functional structure of fish assemblages in streams with different levels of urbanization, as well as, relationships of these patterns with local and regional environmental factors. It was tested the hypothesis that the structure of the fish assemblage in impacted environments shows influence on local and regional scales. Data from 10 streams in a gradient of urbanization in Maringá County, Brazil, were used to characterize fish assemblages' and environmental factors. Discriminant function analysis was used a priori to test differences between streams and environmental factors. Associations between the structure of fish assemblages and environmental factors in local and regional scales were observed with direct gradient analysis (CCA and pCCA) and relative's contribution quantified by inertia partition techniques. Indicator values were used to find characteristic species in streams with different impacts levels. The environmental factors and taxonomic and functional structure of fish assemblages were different in streams with different urbanization levels in regional and local scales. The results evidenced the important role of taxonomic and functional traits to evaluation, management and monitoring urban watersheds where environmental factors act in a hierarchical manner on the structure of fish assemblages.